Physical activity intensity can be accurately monitored by smartphone global positioning system `app` - Gordon, B. A.; Bruce, L.; Benson, A. C. (European Journal of Sport Science, 2016)
Monitoring physical activity is important to better individualise health and fitness benefits. This study assessed the concurrent validity of a smartphone global positioning system (GPS) `app` and a sport-specific GPS device with a similar sampling rate, to measure physical activity components of speed and distance, compared to a higher sampling sport-specific GPS device. Thirty-eight (21 female, 17 male) participants, mean age of 24.68, s = 6.46 years, completed two 2.400 km trials around an all-weather athletics track wearing GPSports Pro™ (PRO), GPSports WiSpi™ (WISPI) and an iPhone™ with a Motion X GPS™ `app` (MOTIONX). Statistical agreement, assessed using t-tests and Bland-Altman plots, indicated an (mean; 95% LOA) underestimation of 2% for average speed (0.126 km·h-1; -0.389 to 0.642; p < .001), 1.7% for maximal speed (0.442 km·h-1; -2.676 to 3.561; p = .018) and 1.9% for distance (0.045 km; -0.140 to 0.232; p < .001) by MOTIONX compared to that measured by PRO. In contrast, compared to PRO, WISPI overestimated average speed (0.232 km·h-1; -0.376 to 0.088; p < .001) and distance (0.083 km; -0.129 to -0.038; p < .001) by 3.5% whilst underestimating maximal speed by 2.5% (0.474 km·h-1; -1.152 to 2.099; p < .001). Despite the statistically significant difference, the MOTIONX measures intensity of physical activity, with a similar error as WISPI, to an acceptable level for population-based monitoring in unimpeded open-air environments. This presents a low-cost, minimal burden opportunity to remotely monitor physical activity participation to improve the prescription of exercise as medicine.